Analysis of wind energy potential of Sakarya-Esentepe region, Turkey - (:unkn) unknown (My University, 2012)
In this study, the data obtained from the measurements made in the wind measurement station established in Sakarya region are evaluated and the wind energy potential of the region is determined. Wind data were used in ten-minute intervals of 12 months from July 2006 to 2007. In statistical examination of the wind energy potential, the Weibull distribution is used. For this purpose, the MATLAB program was developed for numeric analysis. Besides, in analysis of the wind data and energy calculations, Weibull distribution parameters and frequency distribution of wind speed, dominated wind direction, and the region's annual main power density values have also been identified by the using of the WindPRO and WAsP software. The annual Weibull Fig. parameter (k) and scale parameter (c) were determined as 1.81 and 5.12 m/s for 30m height respectively. According to the Weibull distribution, the annual mean wind speed and power density values for 30m hub height are obtained as 4.55 m/s and 121.01 W/m3, respectively. As a result of this work, annual average wind speed and frequency with energy density is expressed as the sector and changing of the region's annual mean wind speed and power density with numerical height were determined. Analyses of the results show that the wind energy potential of Sakarya-Esentepe region is eligible for electrical power production. © Sila Science.
Keywords: WAsP; Weibull distribution; Wind energy; Wind measurement; WindPro